2019
DOI: 10.5897/jat2019.0357
|View full text |Cite
|
Sign up to set email alerts
|

The role of board characteristics on the relationship between International Financial Reporting Standards (IFRS) adoption and earnings management: Evidence from China

Abstract: The purpose of this study is to investigate the effect of International Financial Reporting Standards (IFRS) adopting on earning management by considering the role of board size and board independence. Univariate tests and multivariate regression analysis were employed to test whether the level of earnings management is significantly lower after the adoption of IFRS and whether the role of board size and board independence on constraining the earnings managements is higher after IFRS adoption for a sample of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…For example, Tian et al (2023) deduced that the relationship between BC and IC quality is strengthened when ownership is more concentrated, indicating the vital role of ownership structure in enhancing the effect of BC on IC. Alqatan et al (2019) also observed positive effects of board size and independent director percentage on IC. Additionally, Gutiérrez (2019), Larrain and Urzúa (2015), and Pucheta-Martínez (2019) examined the linkage between OC and corporate governance in Latin America, revealing that higher levels of OC may lead to weaker governance and lower firm value.…”
Section: The Function Of Board Compensation (Bc): Agency Theory and S...mentioning
confidence: 73%
“…For example, Tian et al (2023) deduced that the relationship between BC and IC quality is strengthened when ownership is more concentrated, indicating the vital role of ownership structure in enhancing the effect of BC on IC. Alqatan et al (2019) also observed positive effects of board size and independent director percentage on IC. Additionally, Gutiérrez (2019), Larrain and Urzúa (2015), and Pucheta-Martínez (2019) examined the linkage between OC and corporate governance in Latin America, revealing that higher levels of OC may lead to weaker governance and lower firm value.…”
Section: The Function Of Board Compensation (Bc): Agency Theory and S...mentioning
confidence: 73%
“…In a study conducted by Khaldoon et al (2019), the authors examined the impact of International Financial Reporting Standards (IFRS) adoption on earning management in China by taking into account the importance of board size and board independence. According to the empirical findings, earning management improved with the adoption of IFRS.…”
Section: Literature Review and Hypotheses Development Earnings Manage...mentioning
confidence: 99%